Comparison of agricultural and economic productivity of sustainable and conventional papaya in Michoacan, Mexico - Miranda Ramírez, José Mario; Aguilar García, Omar; Miranda Medina, Diana (Agronomía Mesoamericana, 2020)
Introduction. In Buenavista, Michoacan, Mexico, the area planted with papaya (Carica papaya L.) is of the Maradol Roja variety and most farmers use a conventional agricultural production model, where the productivity and profitability of the crop is not known with certainty. culture; therefore, it is important to know these two variables in order to obtain an efficient production that in the medium term allows them to improve the socio-economic environment of the farmers. Objective. Compare a sustainable agricultural production model against the conventional papaya production model, to identify agricultural production and the cost-benefit ratio. Materials and methods. The experiment was carried out in the municipality of Buenavista, Michoacan, Mexico during 2015. It was characterized by having two experimental units, one treatment per unit [sustainable and conventional] with a simple randomized sampling. Fruit weight, total soluble solids, and fruits per plant were evaluated. Statistical analysis included Levene’s test, Kolmogorov-Smirnov, and Lilliefors test, ANOVA and non-parametric Mann-Whitney U test. Economic analysis was carried out with the indicators: total investment cost, total income, cost-benefit ratio, profitability, and break-even point. Results. The sustainable model showed for fruit weight 1.71 kg, 38.06, fruits per plant, total investment cost of USD 8,736.83 ha-1, cost-benefit ratio of 2.24, and an equilibrium point of 38.47 %. The conventional model showed 2.20 kg in fruit weight, 53.72 fruits per plant, a total investment cost of USD 9,262.03 ha-1, cost-benefit ratio 1.08, and an equilibrium point of 90.11 %. Conclusion. The conventional model was economically unfavorable, so it is suggested to gradually improve it until it becomes profitable. The sustainable model proved to be very economically attractive and to have efficient use of local natural resources.